Synthesis of multi-thiol functionalized polylactic acid, polyhydroxybutyrate and polycaprolactone. (May 2015) - Belkhir, Kedafi; Shen, Hang; Chen, Jianding; Jegat, Corinne; Taha, Mohamed
Abstract : Graphical abstract: Highlights: Multi-thiol functionalized polyesters were synthesized. The products are mainly made of biodegradable segments. The molecular design and the thiol functionality were controllable. High thiol content was obtained: 1.2 · 10 −3 mol SH/g of product. Abstract: Biodegradable multi-thiol functionalized polyesters were synthesized using PLA, PHB and PCL hydroxyl telechelic segments. The structures of these polyesters were designed to endow oligomers with different segment compositions and thiol functionalities. Thiol functionalities between 3 and 7 corresponding to 0.25–1.2 × 10 −3 mol SH/g of product were obtained. Model reactions were carried out before the synthesis of the functionalized polymers. Multi-isocyanate functionalized polymers were first prepared. Then, by reaction with 2-Aminothiophenol, multi-thiol functionalized polymers were selectively prepared. The products were characterized by spectroscopy and titrated to confirm the expected structures. The effects in the different reactions of stoichiometric parameters on the structure, molar mass, thiol functionality and glass transition temperature of these polymers were evaluated.